Análise da atividade clareadora, antioxidante e fotoprotetora do extrato aquoso de Myracrodruon urundeuva e desenvolvimento de um sérum facial multifuncional - Diógenes, Érika Sabóia Guerra (2023)
Myracrodruon urundeuva Fr. Allem. is the scientific designation for the aroeira-dosertão, a large tree, with a tall trunk, straight. It belongs to the Anacardiaceae family and occurs in the caatinga and dry forests, from Ceará to the states of Paraná and Mato Grosso do Sul. Its use is common in the treatment of skin disorders, problems related to respiratory and urinary diseases, as well as an excellent “sitz bath” in postpartum and other gynecological problems. Melasma has a multifactorial pathogenesis. Melanic patches occur, in general, due to an increase in local pigmentation and its treatment must include a multimodal approach with combined therapy that incorporates bleaching agents, antioxidants and photoprotectors. Thus, the present study aims to develop a facial serum with whitening action with the aqueous extract of the leaves of Myracrodruon urundeuva (EAFMU). Initially, a phytochemical analysis of the EAFMU was carried out using nuclear magnetic resonance, quantification of total phenolic compounds, flavonoids and physicochemical and organoleptic characterization . Because hyperchromia is related to a multifactorial origin, the inhibition of the tyrosinase enzyme was analyzed, as well as the chelating capacity, since the enzyme is cupro-dependent. The antioxidant effect was also evaluated by the TBARS, DPPH and hydroxyl radical methods. Scanning was carried out at wavelengths equivalent to UVB and UVA (280 to 400 nm), so a comparison can be made with the spectrum obtained from the benzophenone-3 standard at the same wavelengths; and through Mansur's methodology, the FPS of the EAFMU and standard was obtained. The safety of the extract was evaluated through the cytotoxicity assay in murine fibroblast cells by the Sulforhodamine B method. Subsequently, the facial serum development study (SFMU) was carried out, with the study of pH, viscosity, density, centrifugation test and preliminary and accelerated stability testing. SFMU and the blank (serum without extract) were evaluated at six different times, at low temperature (5,0 ± 2,0 °C), room temperature (25,0 ± 2,0 °C), and high temperature (40,0 ± 2,0 °C). Formulation safety was performed by patch test. EAFMU showed excellent tyrosinase inhibitory action, and at a concentration of 1,500 µg/mL inhibited 76.48% of the enzyme, while kojic acid at the same concentration inhibited 96.16%. It was also demonstrated that the extract acted by chelating the copper ion. In the three antioxidant assays, EAFMU demonstrated satisfactory in vitro activity: at a concentration of 50 µg/mL, it inhibited 49.59% of substances reactive to thiobarbituric acid; 76.46% of the DPPH radical and and 51.07% of the hydroxyl radical. Regarding protection against ultraviolet rays, EAFMU and benzophenone-3 showed SPF of 14.43 and 20.39, respectively. The formulation was developed using 1% EAFMU, the parameters evaluated were organoleptic (appearance, color and odor); physical-chemical (viscosity, density and pH); microscopy and chemical (gallic acid quantification). The formulation was shown to be safe through the patch test, that is, the product did not induce skin irritation and sensitization; as well as being stable. In this way, the aroeira-do-sertão, a plant that is commonly used for various purposes, especially in the northeastern hinterland, proved to have the potential to whiten melasma.